Simulations of the Milky Way’s Central Molecular Zone: II. star formation - Sormani, Mattia C.; Treß, Robin G.; Glover, Simon; Klessen, Ralf S.; Battersby, Cara D.; Clark, Paul C.; Hatchfield, H. Perry; Smith, Rowan J. (Monthly notices of the Royal Astronomical Society, 2020)
The Milky Way’s Central Molecular Zone (CMZ) has emerged in recent years as a unique laboratory for the study of star formation. Here we use the simulations presented in Tress et al. to investigate star formation in the CMZ. These simulations resolve the structure of the interstellar medium at sub-parsec resolution while also including the large-scale flow in which the CMZ is embedded. Our main findings are as follows. (1) While most of the star formation happens in the CMZ ring at $R\gtrsim 100 \, {\rm pc}$, a significant amount also occurs closer to Sgr A* at